Drei-Ebenen-Modell der Familien- und Systemdiagnostik - Hunger-Schoppe, Christina (Psychotherapeut, 2018)
BackgroundFamily and systems diagnostics are a fundamental component within society and higher education. Theories and methods which are easy to communicate increasingly are becoming more important.ObjectiveThis article presents a rationale for future research and intervention heuristics in the field of family and systems diagnostics based on the three-level model, which encompasses four perspectives on social interactions. Selected questionnaires with good psychometric soundness are presented, as well as a selection of research studies for each of these questionnaires, specifically addressing German-speaking populations.Material and methodsThe basic concept is presented with the three-level model published by Cierpka (2008a), graphically depicted by the author. The selection of the family and systems diagnostics questionnaires is based on a priori defined criteria, followed by an electronic search (PsycINFO, PSYNDEX, Google Scholar).ResultsConsidering Germany-speaking populations, three of the four perspectives on social interactions provided by the three-level model are well supported by psychometrically sound questionnaires, including retest reliability and norms, though from some years ago. Most questionnaires refer to dyadic relationships and families as a whole. Questionnaires for the assessment of individual experiences in social systems or triadic relationships are less often available. Most questionnaires perform correlation analyses within the social dyad while triadic interactions are not reported.ConclusionGerman family and systems diagnostics have access to a great variety of well-validated questionnaires to assess social interactions on different levels of complexity. Future research has to consider all perspectives of social interactions, especially taking triadic interactions and the role of adult social interactions for health prevention and clinical treatment processes into account.
Gesehen am 10.10.2019